Health-Related Quality of Life among the Elderly Living in the Community and Nursing Home (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
The increasing number of the elderly population presents special challenges in the health sector with the emergence of degenerative problems and non-communicable diseases (NCD’s) that may decrease the quality of life (QoL). Development in the quality of life of the elderly is an important issue for national security and development. This study using cross-sectional approach, intended to identify the differences in the quality of life among the elderly who live in the nursing homes and the community. The results showed that statistically significant differences were found in variable ages (p001), education background (p0.001), dependency level (p=0.024) for Activity Daily Living and (p0.001) for Instrumental Activity Daily Living) and the overall score of QoL (p=0.036). Based on this finding, the differences approach must be given in meeting the mobility needs and daily activities of the elderly who live in communities and nursing homes.